Lack of knowledge is the leading key for the growing cervical cancer incidents in Bangladesh: A population based, cross-sectional study - Nur E. Alam; Md. Shariful Islam; Fabia Rayyan; Humaira Nur Ifa; Md Imam Ul Khabir; Kamal Chowdhury; A. K. M. Mohiuddin (Public Library of Science (PLoS), 2022)
Introduction Cervical cancer is the second most common gynecological cancer in Bangladesh. Lack of awareness of screening methods, risk factors, and symptoms may lead to presenting most cervical cancers at an advanced stage. We investigated knowledge and awareness of cervical cancer (CCa) among females at the Sheikh Hasina Medical College (SHMC) of Tangail district in Bangladesh. Methods A cross sectional survey was conducted to collect data via a structured questionnaire from SHMC during the period of February 2019 to January 2020. Data on socio-demographic characteristics and knowledge of cervical cancer were collected. Multivariable logistic regression models were used to identify factors associated with having heard and knowledge of cervical cancer. A p-value <0.05 was considered significant. Result Of all the interviews conducted, only 45.2% (493/1090) had heard of cervical cancer as a disease. Women were more likely to be aware of CCa if they were lived in urban areas, had higher education (university level education) and belong to high income families. The study revealed evidence of significant association between marital, literacy, residence and socio-economic status with women's knowledge on cervical cancer (p< 0.05). Conclusion This study serves to highlight that there was impoverished knowledge about cervical cancer among Bangladeshi women. Hence, this indicates the government should take proper steps to raise awareness and knowledge levels via educational programs and health counseling.